Using geolocated tweets for characterization of Twitter in Portugal and the Portuguese administrative regions - Brogueira, G. (2017)
The information published by the millions of public social network users is an important source of knowledge that can be used in academic, socioeconomic or demographic studies (distribution of male and female population, age, marital status, birth), lifestyle analysis (interests, hobbies, social habits) or be used to study online behavior (time spent online, interaction with friends or discussion about brands, products or politics). This work uses a database of about 27 million Portuguese geolocated tweets, produced in Portugal by 97.8 K users during a 1-year period, to extract information about the behavior of the geolocated Portuguese Twitter community and show that with this information it is possible to extract overall indicators such as: the daily periods of increased activity per region; prediction of regions where the concentration of the population is higher or lower in certain periods of the year; how do regional habitants feel about life; or what is talked about in each region. We also analyze the behavior of the geolocated Portuguese Twitter users based on the tweeted contents, and find indications that their behavior differs in certain relevant aspect from other Twitter communities, hypothesizing that this is in part due to the abnormal high percentage of young teenagers in the community. Finally, we present a small case study on Portuguese tourism in the Algarve region. To the best of our knowledge, this work is the first study that shows geolocated Portuguese users' behavior in Twitter focusing on geographic regional use.